IMPLEMENTATION OF ONLINE LEARNING BASED ON EDUCATION LEVEL - Betri, Tigus Juni (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Online learning plays a very important role in this current pandemic. All levels of education must implement online learning because face-to-face meetings are not possible. Many people complain that online learning is not effective. This is due to several thing, for example, the application of online learning requires accuracy to match students with their level of education, both in terms of strategy and application. This article discussed an overview of online learning by analysing the level of education and determining the appropriate technique. The results showed that analysis and preparation steps were needed. Therefore, it is necessary to do the right strategy in online learning activities by determining the techniques used. This is because a technique is not necessarily appropriate for all levels of education. The step must be appropriate for the level of education of the students. Next determine the application and implement the strategy. Keywords: education, online learning, techniques